Identification and Analysis of Genes Underlying Bone Mineral Density by Integrating Microarray Data of Osteoporosis - Zhang, Haihong; Feng, Jinghui; Lin, Zhiguo; Wang, Shuya; Wang, Yan; Dai, Siming; Kong, Weisi; Wang, Yanli; Zhang, Zhiyi (Frontiers in Cell and Developmental Biology, 2020)
Osteoporosis is a brittle bone disease. It is characterized by a reduction in bone mineral density (BMD). In recent years, a number of genes and pathophysiological mechanisms have been identified for osteoporosis. However, the genes associated with BMD remain to be explored. Towards this end, we integrated multiple osteoporosis microarray datasets to identify and systematically characterize BMD-related genes. By integrating the differentially expressed genes from three osteoporosis microarray datasets, 152 genes were differentially expressed between high and low BMD osteoporosis samples in at least two of the three datasets. Among them, 88 were up-regulated in high BMD samples and 64 were up-regulated in low BMD samples. The expression of ZFP36, JUNB and TMEM8A were increased at high BMD samples in all three datasets. Hub genes were further identified by co-expression network analysis. Functional enrichment analysis showed that the gene up-regulated in high BMD were enriched in immune-related functions, suggesting that the immune system plays an important role in osteoporosis. Our study explored BMD-related genes based on osteoporosis microarray dataset integration, providing guidance to other researchers from a new perspective.